PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP MUHAMMADIYAH 6 PADANG - Mayang Sari, Novelia; Husna, Husna; Harisman, Yulyanti (Pendidikan Matematika, 2014)
ABSTRACTThis research is background by the student who less responsibility from assignment which given by teacher and the lack of understanding of mathematical concepts students are still low. The study aims to determine the understanding of mathematical concepts by implementing cooperative learning model Teams Games Tournament (TGT) better than an understanding of mathematical concepts with conventional learning class VII SMP Muhammadiyah 6 padang. This research is experimental, with random design on the subject. The instrument used was an essay test and observation sheets. Hypothesis testing using the U Mann-Whitney test with the MINITAB program obtained p-value = 0.0002 is less than Î±, then reject H0. It can be concluded that the understanding of mathematical concepts with cooperative learning model Teams Games Tournament (TGT) better than an understanding of mathematical concepts with conventional learning students